2006
DOI: 10.1507/endocrj.k06-074
|View full text |Cite
|
Sign up to set email alerts
|

Increased Red Blood Cells in Patients with Metabolic Syndrome

Abstract: We read with great interest the recently published study by Kim et al. [1] on the relationship of red blood cell counts (RBCCs) to metabolic syndrome (MS), and its sex differences. They indicate that RBCCs are not associated with MS components in men and women. Until now, a few studies have reported a positive association of RBCCs, hemoglobin (Hb) and hematocrit with MS [2] or insulin resistance syndrome [3,4], with no mention of sex differences. These reports have provoked debate on red blood cell (RBC)-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Chinese population [21]. Kotani confirmed that red blood cell count is an indicator related to Mets and its components, contrary to Kim's study on Koreans with no relationship discovered between them [22,23]. In this study, RBC was significantly associated with MAFLD in males, with no such trendin females.…”
Section: Plos Onecontrasting
confidence: 64%
See 1 more Smart Citation
“…Chinese population [21]. Kotani confirmed that red blood cell count is an indicator related to Mets and its components, contrary to Kim's study on Koreans with no relationship discovered between them [22,23]. In this study, RBC was significantly associated with MAFLD in males, with no such trendin females.…”
Section: Plos Onecontrasting
confidence: 64%
“…Using a longitudinal cohort design, Zhong et al discovered that RBC is not only connected with the incidence of NAFLD but also the severity of incident NAFLD development in Chinese population [ 21 ]. Kotani confirmed that red blood cell count is an indicator related to Mets and its components, contrary to Kim’s study on Koreans with no relationship discovered between them [ 22 , 23 ]. In this study, RBC was significantly associated with MAFLD in males, with no such trendin females.…”
Section: Discussionmentioning
confidence: 73%
“…These results are along the line of already published data reporting that subjects affected by MS exhibit a higher count of RBCs compared to metabolically healthy subjects. It has been reported that, despite the presence of chronic inflammation which has suppressive erythropoietic effects, erythropoiesis correlates with central obesity and insulin resistance [54] and that RBC count is, even though still within normal range, significantly higher in the presence of MS for each sex [55].…”
Section: Discussionmentioning
confidence: 99%